Gender inequalities in rural labour markets: The role of corporate social responsibility in Niger Delta, Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2022)
Purpose - The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on women's involvement in rural labour market in the Niger Delta region of Nigeria. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially crosssectional, describing and interpreting the current situation. A total of 768 respondents were sampled across the rural areas of the Niger Delta region. Findings - The results from the use of a combined propensity score matching and logit model indicate that CSR of the MOCs using GMoU model has recorded little but significant success in improving women's participation in the labour market by freeing women's time through labour-saving technologies and the provision of public services, raising women's capital through education, eliminating discriminatory employment practices and capitalizing on public works programmes. Practical implications -This suggest that the underlining causes of gender inequality in rural labour markets are institutional, including both social norms and the structure of labour market organizations; and can be holistically tackled through corporate social responsibility programmes, government policies, and building the strength of women in labour organizations. Social implications - This implies that reducing rural poverty requires not just the barriers to women's participation in decent employment, but aiming for a policy that helps to change people's perceptions of what is possible, beneficial, and fair; fosters cooperative action; and strengthens women's bargaining power in the work place, the home, and the market place. Originality/value - This research contributes to the gender debate in agriculture from a CSR perspective in developing countries and rationale for demands for social project by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Gender; rural labour market; corporate social responsibility; multinational oil companies; sub-Saharan Africa